SN 2014ab: an aspherical Type IIn supernova with low polarization. Issue 3 (27th August 2020) - Bilinski, Christopher; Smith, Nathan; Williams, G Grant; Smith, Paul; Andrews, Jennifer; Clubb, Kelsey I; Zheng, WeiKang; Filippenko, Alexei V; Fox, Ori D; Hosseinzadeh, Griffin; Howell, D Andrew; Kelly, Patrick L; et al.
ABSTRACT: We present photometry, spectra, and spectropolarimetry of supernova (SN) 2014ab, obtained through ∼200 d after peak brightness. SN 2014ab was a luminous Type IIn SN ( MV < −19.14 mag) discovered after peak brightness near the nucleus of its host galaxy, VV 306c. Pre-discovery upper limits constrain the time of explosion to within 200 d prior to discovery. While SN 2014ab declined by ∼1 mag over the course of our observations, the observed spectrum remained remarkably unchanged. Spectra exhibit an asymmetric emission-line profile with a consistently stronger blueshifted component, suggesting the presence of dust or a lack of symmetry between the far side and near side of the SN. The Pa β emission line shows a profile very similar to that of H α, implying that this stronger blueshifted component is caused either through obscuration by large dust grains, occultation by optically thick material, or a lack of symmetry between the far side and near side of the interaction region. Despite these asymmetric line profiles, our spectropolarimetric data show that SN 2014ab has little detected polarization after accounting for the interstellar polarization. We are likely seeing emission from a photosphere that has only small deviation from circular symmetry in the plane normal to our line of sight, but with either large-grain dust or significant asymmetry in the density of circumstellar material or SN ejecta along our line of sight. We suggest that SN 2014ab and SN 2010jl (as well as other SNe IIn) may be events with similar geometry viewed from different directions.